The Muslim extremist discourse constructing us versus them - Jan, Faizullah (Lexington Books, 2015)
Muslim Extremist Discourse analyzes the discourse of militant extremists. Newspapers published by extremists play a critical role in securing and maintaining public support for militant organizations. This book provides an understanding of extremist narratives and the ways they feed the broader militant discourse.